Design of a Computerized Library System Application for SMK Negeri 1 Buer, Sumbawa Regency - Putra, Bintang; Ekastini (Management of Information System Journal, 2025)
This research aims to design a computerize library information system at SMKN 1 Buer to replace the manual system still used in managing book collections, recording transactions, and generating reports. The existing manual system is deemed inefficient, prone to recording errors, and complicates the process of searching and data recapitulation. The methodology used in this research is a mixed-methods approach, with data collection techniques including interviews and documentation. The system design was carried out using an object-oriented approach with the help of Unified Modelling Language (UML) tools, which include use case diagrams, activity diagrams, class diagrams, and ERD. Admins and members can use the web-based digital library system for login, borrowing, returning, and printing reports, thanks to the design results. This system is expected to improve service efficiency and data accuracy and facilitate users in accessing library information online.